The Effect of Service Quality and Perceived Value on Customer Satisfaction Mediated by Trust - Mathesa, Justin Ricky; Liestyana, Yuli; Utami, Yekti; Wahyuningsih, Tri; Oetomo, Hadi; Tugiyo, Tugiyo (Strata Business Review, 2025)
This study investigates the influence of service quality and perceived value on customer satisfaction, with trust functioning as a mediating variable. The research was conducted among PBPU/Mandiri BPJS Health Insurance participants registered at the Yogyakarta JKN BPJS Health Branch. Using a quantitative approach, data were collected through purposive sampling, resulting in 110 respondents who completed a structured questionnaire. Measurements were based on a Likert scale, and data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (SmartPLS 3.0). The results indicate that all indicators used in the study demonstrate strong loading factor values, confirming their reliability as research instruments. The R-Square value shows that service quality, perceived value, and trust collectively explain 85.9% of the variance in customer satisfaction, while the remaining 14.1% is influenced by other unexamined factors. Findings further reveal that both service quality and perceived value significantly and positively affect trust and customer satisfaction. Moreover, trust is found to effectively mediate the relationship between service quality and perceived value on customer satisfaction. These results highlight the crucial role of trust in enhancing customer satisfaction within the BPJS Health Insurance service context.